2006
DOI: 10.1038/ng1732
|View full text |Cite
|
Sign up to set email alerts
|

Variant of transcription factor 7-like 2 (TCF7L2) gene confers risk of type 2 diabetes

Abstract: We have previously reported suggestive linkage of type 2 diabetes mellitus to chromosome 10q. We genotyped 228 microsatellite markers in Icelandic individuals with type 2 diabetes and controls throughout a 10.5-Mb interval on 10q. A microsatellite, DG10S478, within intron 3 of the transcription factor 7-like 2 gene (TCF7L2; formerly TCF4) was associated with type 2 diabetes (P = 2.1 x 10(-9)). This was replicated in a Danish cohort (P = 4.8 x 10(-3)) and in a US cohort (P = 3.3 x 10(-9)). Compared with non-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

83
1,570
14
32

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,018 publications
(1,721 citation statements)
references
References 23 publications
83
1,570
14
32
Order By: Relevance
“…Data are expressed as mean+SEM. *p< 0.05 si5-LO1 and/or si5-LO2 vs scramble siRNA genes controlling beta cell function also play an important role in adult-onset type 2 diabetes, suggesting that insulin secretion-related mechanisms may make more significant genetic contributions to common forms of type 2 diabetes than previously recognised [22][23][24][25][26]. Thus, identification of novel pathways regulating beta cell function and/or insulin secretion may lead to a better understanding of type 2 diabetes and its underlying aetiology.…”
Section: Discussionmentioning
confidence: 99%
“…Data are expressed as mean+SEM. *p< 0.05 si5-LO1 and/or si5-LO2 vs scramble siRNA genes controlling beta cell function also play an important role in adult-onset type 2 diabetes, suggesting that insulin secretion-related mechanisms may make more significant genetic contributions to common forms of type 2 diabetes than previously recognised [22][23][24][25][26]. Thus, identification of novel pathways regulating beta cell function and/or insulin secretion may lead to a better understanding of type 2 diabetes and its underlying aetiology.…”
Section: Discussionmentioning
confidence: 99%
“…Grant et al (2006) identified DG10S478 located in intron 3-exon 4 of the TCF7L2 gene on chromosome 10q25.2 (in a well-defined LD block of 92.1 kb based on CEU HapMap v16; GenBank NM 030756) that had an r 2 of 0.95 with the rs12255372 SNP [6]. The authors suggest that the TCF7L2 variants increase T2D risk by altering proglucagon gene expression [6] in enteroendrocrine cells [24] via the Wnt signaling pathway [26]. Florez et al (2006) reported that individuals with the TT genotype have decreased insulin secretion [7].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in TCF7L2 have been associated with disease susceptibility. Specifically, Grant et al (2006) demonstrated that a polymorphism in TCF7L2 is associated with increased risk of type II diabetes (T2D) [6][7][8][9][10][11][12] by impaired beta-cell function [7,9]. Epidemiologic studies have suggested that hyperinsulinemia may be related to the risk of colon adenoma and cancer [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, still lacking is knowledge on whether patients with LADA have the same frequency of the few type 2 diabetes susceptibility genes that have reproducibly been associated with type 2 diabetes, e.g. the Pro12Ala single-nucleotide polymorphism in PPARG, the E23K SNP in KCNJ11, or the recently described polymorphisms in TCF7L2 [13][14][15].…”
mentioning
confidence: 99%